GENERATIVE AI IN TEACHING INTERNATIONAL FINANCIAL TECHNOLOGIES THROUGH SIMULATIONS OF OPEN BANKING AND CBDC PAYMENTS - G. M. Bakoeva (Modern American Journals, 2026)
The article examines the use of generative artificial intelligence (AI) in teaching the course “Modern International Financial Technologies” within a simulation-based approach. The study was conducted in two stages: first, an analysis of the regulatory framework and the practices of digital banks in Uzbekistan; second, the development, with AI, of varied cases and synthetic datasets. Four modules are presented: ISO 20022, open banking, CBDC/stablecoins, and regtech KYC/AML. AI acts as a scenario designer and tutoring assistant: it creates “noisy” data, models negative cases, and supports the verification of solutions. The results show that the simulation format enhances understanding of payment architectures, develops API design skills, and increases student engagement.
Keywords: Generative AI, open banking, CBDC, simulations in education, financial technologies, digital transformation.